2013
DOI: 10.3109/11038128.2013.779321
|View full text |Cite
|
Sign up to set email alerts
|

Three very old men's experiences of mobility device use over time

Abstract: 397-405. DOI: 10.3109/11038128.2013.779321 General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research.• You may not further distribute the material or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 26 publications
(18 reference statements)
1
21
0
1
Order By: Relevance
“…The use of assistive devices increases and implies changes in use and need also in a short-term perspective in very old age (studies 19,24). This is particularly true for mobility devices (MDs) (studies 19, 23) as they support independence and facilitate participation (studies 12, 20,22). At the macro level there are marked differences among countries, with less availability of MDs in Eastern than in Western European countries (study 24).…”
Section: Personal and Environmental Influences On Aging In Placementioning
confidence: 99%
See 2 more Smart Citations
“…The use of assistive devices increases and implies changes in use and need also in a short-term perspective in very old age (studies 19,24). This is particularly true for mobility devices (MDs) (studies 19, 23) as they support independence and facilitate participation (studies 12, 20,22). At the macro level there are marked differences among countries, with less availability of MDs in Eastern than in Western European countries (study 24).…”
Section: Personal and Environmental Influences On Aging In Placementioning
confidence: 99%
“…At the macro level there are marked differences among countries, with less availability of MDs in Eastern than in Western European countries (study 24). Positive outcomes of MD use aside, the devices add to the complexity of home and health dynamics and are important in P-E interactions (studies 20,22), particularly among those aging with chronic disease (study 9). Access to different types of MDs, and their forms and functions are important for optimal use (studies 20,22).…”
Section: Personal and Environmental Influences On Aging In Placementioning
confidence: 99%
See 1 more Smart Citation
“…AT has been shown to positively support the changing needs of older people as their mobility declines, assisting continued domestic independence and social involvement . Kylber et al undertook a study in Sweden which found that the provision of appropriate AT facilitated feelings of support and safety which assisted with the continuation of ADL. Asghar et al also assert that ATs are commonly used for the well‐being of people with dementia.…”
Section: Introductionmentioning
confidence: 99%
“…However, for the case of the exploration of elderly persons' values we do not see this as a problem, given the goal of our research. The interviews were held to gain deep insight into the individual lives and to identify new possibilities for new product or service designs, and by that build upon the knowledge base on mobility device use (Kylberg, Löfqvist, Phillips, & Iwarsson, 2013). Such possibilities are most often not found in large numbers.…”
Section: Limitationsmentioning
confidence: 99%